THE EFFECT OF DISTRIBUTIVE JUSTICE, INTERACTIONAL JUSTICE, AND LEADERSHIP STYLE ON INNOVATIVE WORK BEHAVIOR WITH INTERVENING JOB SATISFACTION VARIABLES AT PT MEDIANUSA PERMANA, BATAM CITY - Erick Santana; Bambang Satriawan; Mohamad Gita Indrawan; Muammar Khaddafi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The purpose of this study was to determine and analyze the effect of Distributive Justice, Interactional Justice, and Leadership Style on Innovative Work Behavior with intervening variable Job satisfaction at PT Medianusa Permana Batam City. The method used is a questionnaire and distributed to 100 respondents. Analysis of statistical data using SEM PLS (Structural Equation Modeling Partial Least Square) and using path analysis to examine the pattern of the relationship between the influence of the dependent variable on the independent, both direct and indirect effects with SMART PLS 3.0 software. The results in the study indicate that Distributive Justice has a positive and significant effect on job satisfaction with a p-value of 0.000 <0.05, Interactional Justice has a positive and significant effect on job satisfaction with a p-value of 0. 003 < 0.05. Leadership Style has a positive and significant effect on job satisfaction with a p-value of 0.040 <0.05. Job satisfaction has a positive and significant effect on Innovative Work Behavior with a p-value of 0.008 <0.05. Distributive Justice has a positive and significant effect on Innovative Work Behavior with a p-value of 0.005 <0.05. Interactional Justice has a positive and significant effect on Innovative Work Behavior with a p-value of 0.008 <0.05. Leadership Style has a positive and significant effect on Innovative Work Behavior with a p-value of 0.032 <0.05. Job Satisfaction mediates the effect of Distributive Justice and Innovative Work Behavior with a p-value of 0.005 <0.05. Job Satisfaction mediates mediates the effect of Interactional Justice and Innovative Work Behavior with a p-value of 0. 019 < 0.05. Job Satisfaction mediates the effect of Leadership Style and Innovative Work Behavior. with a p-value of 0.008 < 0.05.